(untitled) (Международный научный журнал «Инженер», 2026)
Studies have shown that the mixing device uses hydrodynamic cavitation principle of the greatest interest from the point of view of obtaining a highly dispersed finished product, with large – scale production of low – power consumption and high reliability of operation of the mixing device. Implemented definition of physical modeling and mathematical model of the process. Defined the optimal basic geometric characteristics of the hydrodynamic jet dispersants – cavitators.